Design for procurement: What procurement driven design initiatives result in environmental and economic performance improvement?. Issue 1 (January 2017) - Brewer, Barry; Arnette, Andrew N.
Abstract: This study examines the role of procurement professionals in new product design. Specifically, it evaluates which factors play an important role in driving design for procurement (DFP) environmental and economic results. The factors early supplier involvement, standardization, lead time reduction, environmental sourcing, supply base maintenance, and core competence focused sourcing are regressed on diverse DFP performance outcomes. Data were collected via survey for a series of procurement focused items capturing the activities and characteristics for new product design and performance. Several major findings were supported through the analysis that enhance academic and managerial knowledge. Standardization positively impacted economic performance measures that focused on new product development and operational outcomes. Supply based maintenance was the strongest DFP initiative driving operational performance. Environmental sourcing positively affected all environmental performance measures, but was not related to economic performance. Highlights: DFP initiatives contribute positively to environmental & economic NPD performance. Environmental DFP improves waste & hazard reduction, recycling & input reuse. DFP standardization drives economic and operational performance.